(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2021)
The prevailing premise, and at the same time, the basis for the creation of a state with its inherent rights, shows and, above all, indicates the existence of a civil society. The creation of such a society in our country is and remains the basic idea and goal of transformation and the introduction of modernized reforms in Kazakhstan. In order to consider and try to reveal the concepts of the relationship between the legal state and the civil society, there is an acute and extreme need for a preliminary analysis and definition of the proposed concepts. That is, it is necessary to define these concepts. In the Kazakh legal science and literature. It is often defined that a legal entity, namely a state – is a state in which the rule of law is practically determined, a state in which power is based on law, is limited by it and is implemented through it. Our attention is drawn to all the distinctive and at the same time significant factors that characterize exactly and only the state with the preservation of all norms and rights. In the current situation, the Kazakh society, namely the state with the preservation of all rights, passes the stage of the most active and at the same time steadily and actively developing establishment. The basis for its comprehensive growth was precisely the fact that the society is based and focused on the rule of law and the law, on the preservation and revival of the basic values of people and citizens of the world. Key words: Social state, Constitution, welfare of the population, civil society, Macroeconomics, citizens ‘ rights, democracy, social norms, social protection.